Impact of Seasonal Variations on Semen Parameters: A Retrospective Analysis of Data from Subjects Attending a Tertiary Care Fertility Centre - Anitha Malathi; Ramesh P. Iyer; Reji Mohan; Sheila Balakrishnan (Journal of Human Reproductive Sciences)
Background: Seasonal variations in semen parameters have been detected in many previous studies, mostly conducted in the West and Mediterranean countries. Located in a tropical region, we have only three seasons – summer, winter and rainy season. Literature search did not reveal studies from Indian subcontinent. Aims: Our objective was to find if our climate produced seasonal variations in semen parameters such as sperm concentration (SC), total motile SC, morphology and vitality, which may have implications in fertility management. Settings and Design: This is a descriptive study, conducted at a tertiary level hospital. Semen analysis reports of male partners of all infertile couples during the 4-year period from 2019 to 2022 were analysed. Materials and Methods: The data were collected from records of all infertile couples registered for the treatment in the department during the study period. Semen analysis reports of male partners of all infertile couples attending outpatient department of the Reproductive Medicine Department during the 4-year period from January 2019 to December 2022 were collected. The data of azoospermic and severe oligospermic (<5 million/mL) men and those receiving hormone treatment were excluded. Statistical Analysis Used: Data were analysed using SPSS 23 and variables expressed as mean and standard deviation. Changes in mean values over years and over seasons were evaluated using F-test. Post hoc analysis was done using Sidak method. P < 5% was considered statistically significant. Results: The data of 2326 patients were analysed. SC was lowest during summer but was not statistically significant. Sluggishly motile sperm per cent was maximum in rainy season (P = 0.002). Post hoc analysis showed significant variations in summer samples compared to both rainy and winter seasons. Head defect (HD) and tail defects showed a significant seasonal variation (P = 0.011 and P = 0.024, respectively), lowest HD seen in rainy season. Conclusion: Semen parameters showed seasonal variations, with favourable features in colder climates, and may need to be considered in infertility management, especially if the male is oligospermic.